Modified Citrus Pectin Prevents Blood-Brain Barrier Disruption in Mouse Subarachnoid Hemorrhage by Inhibiting Galectin-3. Issue 11 (November 2018) - Nishikawa, Hirofumi; Liu, Lei; Nakano, Fumi; Kawakita, Fumihiro; Kanamaru, Hideki; Nakatsuka, Yoshinari; Okada, Takeshi; Suzuki, Hidenori
Abstract : Background and Purpose—: Plasma levels of galectin-3—a matricellular protein—are increased after aneurysmal subarachnoid hemorrhage (SAH), but the functional significance remains undetermined. This study was conducted to evaluate whether modified citrus pectin (MCP; galectin-3 inhibitor) prevents post-SAH early brain injury, focusing on blood-brain barrier disruption. Methods—: C57BL/6 male adult mice (n=251) underwent sham or filament perforation SAH modeling, followed by a random intracerebroventricular injection of vehicle or drug at 30 minutes post-modeling. First, vehicle-treated and 0.8, 4, 16, or 32 µg MCP-treated mice were assessed by neuroscore and brain water content at 24 and 48 hours post-modeling. Second, Evans blue extravasation, Western blotting, coimmunoprecipitation and immunostaining were performed in vehicle-treated or 4 µg MCP-treated mice at 24 hours post-modeling. Third, vehicle or R-galectin-3 (recombinant galectin-3) was administered to SAH mice simultaneously with vehicle or MCP, and neuroscore and Evans blue extravasation were evaluated at 24 hours post-modeling. Fourth, vehicle or R-galectin-3 was administered to MCP-treated SAH mice at 24 hours, and neuroscore and IgG immunostaining were evaluated at 48 hours post-SAH. Results—: Among tested dosages, 4 µg MCP showed the best neuroprotective effects as to preventing neurological impairments and brain edema at 24 to 48 hours post-SAH. Four micrograms MCP attenuated post-SAH blood-brain barrier disruption and galectin-3 upregulation in brain capillary endothelial cells, associated with inactivation of ERK (extracellular signal-related kinase) 1/2, STAT (signal transducer and activator of transcription)-3, and MMP (matrix metalloproteinase)-9, and the consequent preservation of a tight junction protein ZO-1 (zonula occludens-1). Coimmunoprecipitation assay demonstrated physical interactions between galectin-3 and TLR (Toll-like receptor) 4. R-galectin-3 blocked the neuroprotective effects of MCP. Conclusions—: MCP prevents post-SAH blood-brain barrier disruption possibly by inhibiting galectin-3, of which the mechanisms may include binding to TLR4 and activating ERK1/2, STAT-3, and MMP-9. This study suggests galectin-3 to be a novel therapeutic target against post-SAH early brain injury. Abstract : Supplemental Digital Content is available in the text.